PENENTUAN HARGA JUAL SAGU TUMBU PADA HOME INDUSTRY IBU SAPHIA DI NEGERI MORELA MALUKU TENGAH - LITAMAHUPUTTY, JACOMINA VONNY; Manilet , Safani (Journal of Applied Accounting, 2022)
This study aims to determine the selling price of sago tumbu at Ibu Sapia's home industry. Research data comes from primary data obtained directly from the object of research and secondary data obtained from books and other references related to the problem under study. The analysis technique used is quantitative analysis by calculating the selling price of sago grown per fruit using the cost plus pricing method. The results of the study show that the selling price of sago tumbu set by Sapia's mother is lower by calculating the selling price based on the cost plus pricing method.